Distribution of Sodium and Diffusion Mechanism in Sodium Silicate Liquid - Nguyen, Thi Thanh Ha (H. : ĐHQGHN, 2019)
Molecular dynamic simulation is employed to study the structural properties and diffusion mechanism in sodium silicate (Na2O.4SiO4). Structural characteristics are clarified through the pair radial distribution function, distribution of SiOx coordination units, network structure. The simulation results reveal that the structure of Na2O.4SiO4 liquid consists of one Si-O network that is mainly formed by SiO4 units. The spatial distribution of sodium is non-uniform; sodium tends to be in the non-bridging oxygen-simplexes and in larger-radius simplex. Moreover, the sodium density for non-bridging oxygen region is significantly higher than the one for others region. Further, we find that Si and O diffuse by bond break-reformation mechanism, while the motion of Na consists of two parallel processes. Firstly, Na atoms hop from one to another O within a disordered network where each bridging oxygen (BO) has one site, while a non-bridging oxygen (NBO) possesses two sites. The average resident time for Na staying near NBO is much longer than that near BO.